The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4999/uhod.171773
|View full text |Cite
|
Sign up to set email alerts
|

The Three Year Follow-up of CML Patients Treated with First-line Generic and First-line Branded Imatinib in Bosnia and Herzegovina.

Abstract: Imatinib mesylate, a selective BCR-ABL tyrosine kinase inhibitor, has been well established as the standard of care for chronic myeloid leukaemia patients. In this study, we compared clinical outcomes of patients who received first-line Glivec (Group 1) with patients who received first-line generic imatinib (Group 2) in Bosnia and Herzegovina with three years follow-up of therapy. At 24 months of therapy, the achievement of complete cytogenetic response and major molecular response were comparable between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Results from previous studies in Bosnia showed that there was no significant difference in the overall survival and achievement of CCyR between front-line branded imatinib and front-line generic imatinib. [20][21][22] Delayed targeted treatment significantly affected all CML patient outcomes, including survival and cytogenetic and molecular response. However, recent study that analyzed effects of delayed therapy in GIST patients showed that patients who received immediate imatinib therapy for < 1 year did not show better clinical outcomes compared to patients who received the same duration of therapy but had to wait > 6 months for the start of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies in Bosnia showed that there was no significant difference in the overall survival and achievement of CCyR between front-line branded imatinib and front-line generic imatinib. [20][21][22] Delayed targeted treatment significantly affected all CML patient outcomes, including survival and cytogenetic and molecular response. However, recent study that analyzed effects of delayed therapy in GIST patients showed that patients who received immediate imatinib therapy for < 1 year did not show better clinical outcomes compared to patients who received the same duration of therapy but had to wait > 6 months for the start of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had worse responses to the therapy, progression or transformation of the disease, and lower survival rate (112). It was shown that generic versions of imatinib in Bosnia and Herzegovina (Anzovip, Meaxin, Plivatinib) are cost-effective, and response to the therapy was similar to the response to Glivec (115)(116)(117). In 2011, nilotinib (Tasigna, Novartis, second-generation TKI) became available as front-or second-line therapy, and it was designed to overcome specific BCR-ABL1 mutations in imatinib-resistant patients (85,87,(118)(119)(120)(121).…”
Section: Molecular Diagnostics Of Myeloid Malignancies In Bosnia and Herzegovinamentioning
confidence: 99%